2019
DOI: 10.1080/14647273.2019.1567945
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte donation disclosure decisions: a longitudinal follow-up at middle childhood

Abstract: Few studies have captured oocyte donation (OD) parents' decision processes about intended and actual disclosure over time. Likewise, OD children's perceptions about their family composition during middle childhood is underexplored. To address these gaps, a longitudinally followed cohort of OD recipient families was invited to participate in a qualitative, follow-up study. With an 86% response rate after 12 years, families were comprised of oocyte recipient mothers (n = 6) and biological fathers (n = 6) represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 101 publications
0
38
1
Order By: Relevance
“…Among these parents, the greater confidence they had in their ability to talk with the child about his/her genetic origin, the less they were inclined to initiate sharing this information during the coming year. This is a somewhat surprising finding as previous research has shown that parents frequently report uncertainty about how to talk with their child as a major obstacle for disclosure ( Readings et al , 2011 ; Applegarth et al , 2016 ; Hershberger et al , 2019 ). The present results indicate that some parents had made a deliberate decision to postpone disclosure until their child was older, which might be considered to be in contrast to the message from the fertility clinics that parents should start sharing information about the donor conception with the child from an early age ( The National Board of Health and Welfare, 2004 ).…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Among these parents, the greater confidence they had in their ability to talk with the child about his/her genetic origin, the less they were inclined to initiate sharing this information during the coming year. This is a somewhat surprising finding as previous research has shown that parents frequently report uncertainty about how to talk with their child as a major obstacle for disclosure ( Readings et al , 2011 ; Applegarth et al , 2016 ; Hershberger et al , 2019 ). The present results indicate that some parents had made a deliberate decision to postpone disclosure until their child was older, which might be considered to be in contrast to the message from the fertility clinics that parents should start sharing information about the donor conception with the child from an early age ( The National Board of Health and Welfare, 2004 ).…”
Section: Discussionmentioning
confidence: 67%
“…The present results indicate that some parents had made a deliberate decision to postpone disclosure until their child was older, which might be considered to be in contrast to the message from the fertility clinics that parents should start sharing information about the donor conception with the child from an early age ( The National Board of Health and Welfare, 2004 ). However, the perception that the child is too young and needs to reach sufficient maturity to understand donor conception is a commonly reported reason to postpone disclosure ( Indekeu et al , 2013 ; Hershberger et al , 2019 ). This finding may also be related to parents’ desire to protect the family from potential stigmatization by limiting information about the donor conception to a small circle, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations